Validação da nomenclatura de diagnósticos, resultados e intervenções de enfermagem para a clínica cirúrgica do hospital universitário da UFPB - Cunha, Ana Carolina Regis da (2017)
Introduction: The validation of the surgical clinic nomenclature by ICNP® is a decisive step as to analyse the effectiveness of this tool in nursing clinical practice. Objective: To carry out the content and clinical validation of diagnosis’ nomenclature, results and nursing interventions for hospitalised clients at school hospital’s surgical clinic. Methodology: It is a methodological study with embodied quantitative and qualitative approach, where was performed the content and clinical validations of the diagnostic’s wording, results and nursing interventions for the school hospital’s surgical clinic. This paper was submitted to the research ethics committee receiving the CAAE 43249415.0.0000.5183. Results: The 67 nursing diagnostics of surgical clinic nomenclature were mapped according to the diagnostics’ definitions from 2015’s ICNP®, yielding 19 listed and 48 unlisted concepts, henceforth, 8 professionals carried out the validation of the operational definitions’ content of nursing diagnostics, providing 46 approved and 21 denied. Regarding clinical validation, 25 case studies concerning hospitalised clients from July to October of 2016 were conducted. It was catalogued 149 nursing diagnostics for the 25 case studies, distributed among 29 nursing diagnostic concepts. The most frequent nursing diagnostics were as follows: Pain, Disturbed sleep, Risk of infection, Harmed skin integrity and Anxiety. It was listed 330 nursing interventions for the 25 case studies, 72 nursing interventions remained when recurrences were eliminated. Conclusion: The content validation improves the nomenclature, updating its content and promoting the facility in its employment and the clinical validation brings the surgical clinic routine’s existence, operationalizing the nomenclature and verifying its usefulness for assistance practice.